Efektivitas Layanan Bimbingan Kelompok Terhadap Perilaku Konformitas - Indah Jelita Harefa; Elizama Zebua; Famahato Lase; Hosianna Rodearni Damanik (Departement of Mathematics Education, 2024)
Group guidance services (GGS) can alleviate the problem of peer conformity behavior and turn it into good behavior in students. The aim of this research is to reveal the effectiveness of GGS on students' conformity behavior, using quantitative research methods, one group pretest-posttest design experiments. Data is collected by tests and analyzed quantitatively and the results are described. The research population was all class XI students at SMA Permata Kasih Gunungsitoli and the sample was drawn by purposive sampling from a class The research results concluded that the GGS provided by counselors were very effective in alleviating, improving and solving problems of conformity behavior in students. Before being given the GGS, their peers' conformity behavior was very bad, whereas after being given the service, their conformity behavior changed to very good behavior. This is proven by the post-test results which show that the conformity behavior of students from 7 research subjects found a positive increase in their behavior as a result of providing treatment, namely GGS. It was also found that 6 students behaved moderately with a percentage level of 24% and 19 students or 76% whose behavior was high or very good. This means that providing GGS is very effective in improving student conformity behavior. The results of the treatment, namely the difference between the pre-test and post-test, have an average total of 22.24 with an N-Gain test result of 0.89 or 89.43%, so it can be stated that BKp services can have a good impact. It is recommended for guidance and counseling teachers or school counselors to plan and implement GGS to alleviate conformity problems and for students to follow them well.